Density, size and composition of howler monkeys, Alouatta palliata (Atelidae) and white-faced monkeys, Cebus imitator (Cebidae) in dry forest and reduced canopy areas, Costa Rica - MARTINEZ DE ZORZI, VICTORIA ANTONELLA (2025)
Introduction: The size, density, and composition of primate social groups are essential for understanding group dynamics and determining population management plans for primate conservation. Objective: To determine the size, density, and composition of howler monkeys (Alouatta palliata) and white-faced monkey (Cebus imitator) groups in dry forest environments and areas of reduced canopy in Palo Verde National Park, Costa Rica. Understanding how these species respond to different environments has important implications for conservation and reforestation efforts. Methods: Field sampling was carried out during February 2023 during the peak hours of primate activity (6:00-12:00 and 14:00-18:00). The individuals of both primate species were counted, recognizing the groups found in both types of environments (dry forest and reduced canopy areas). Results: Howler monkey group sizes were significantly larger in dry forests and at a higher percent of canopy cover. As for white-faced monkeys, a higher density was recorded in dry forests compared to the last census in 1987. Conclusion: Greater availability of resources (abundance of food and shelter sites) in closed environments favors the presence of a greater number of howler monkeys. Our analyses show that group size in this primate species depends on the type of environment. This study highlights the importance of long-term monitoring and studies of these parameters in wild primate groups.